Failure analysis of a landslide along the Mangla reservoir rim near Khaliqabad, Pakistan. Issue 4 (12th April 2021) - Mehmood, Fatima; Farooq, Khalid
Abstract : After the raising of the Mangla dam in Pakistan in 2010, a maximum reservoir impoundment level of 378.5 m was achieved in September 2014. The reservoir drawdown was started on 29 September 2014, and a landslide occurred on Mirpur–Kotli Road near Khaliqabad on 27 November 2014. This landslide took place due to the failure of a slope along the reservoir rim. This study was undertaken to investigate the causative factors of the Khaliqabad landslide. Site visits were carried out for recording field observations and collection of soil samples. The soil was subjected to different laboratory tests for the determination of its index and engineering properties. These soil parameters were used in Slope/W and integrated Seep–Slope/W analyses to study the effect of density, degree of saturation and reservoir drawdown on the slope stability. The ultimate reduction in the shear strength of the soil due to saturation with simultaneous removal of the stabilising effect of the reservoir was the main triggering factor. The results showed that the factor of safety dropped from 1.28 to 0.85 over a period of 60 days. The findings of this study can serve as a guideline for the modelling of slopes experiencing a reservoir drawdown scenario with the consideration of more realistic distribution of soil moisture/properties across the slope.